Language-Related Hermeneutic Aspects of the Mythology of Modern Communicative Practice - Usmanov Muhriddin Abdimuratovich (Zien Journals, 2022)
This article reveals specific aspects of mythology in modern communicative practice. In addition, the philosophical features of mythology related to language have been interpreted. The content and essence of mythology have also been revealed by philosophers from a modern point of view. Again, aspects of mythology related to language, logos, nature, and man of modern philosophy are revealed.
Keywords: man-nature; mythology; myth; logos